Pengaruh Kompensasi dan Kepemimpinan Transformasional terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening pada Pegawai Dinas Lingkungan Hidup Kabupaten Ponorogo - darmawan, rohadi (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The general purpose of this research is to test and analyze the influence of compensation and leadership style on the employees' performance with the satisfaction of working as a variable intervening in the employees of the district environmental office of Ponorogo. The population in this study was all of the district's environment officers Ponorogo as many as 86 people. In this study used census methods. The data of this research is the primary data by the respondent filling the questionnaire. Once collected data is conducted test instruments consisting of classical assumptions test include multicollinearity test, test normality, autocorrelation test, heteroscedasticity test, analysis techniques using pathway analysis, Test t, Test F, coefficient of determination (R2). The results showed that) the compensation was positively and significantly influential on the employee's performance, the compensation was positively and significantly influential on employee satisfaction, the transformational leadership was positively influential and significant impact on employee performance, transformational leadership is positive and significant in respect to performance satisfaction, job satisfaction positively and significantly impact on employee performance, variable work satisfaction is not effective as a intervening variable on the influence of compensation to employee performance, and variable work satisfaction is ineffective as an intervening variable on the influence of transformational leadership towards employee performance.Â Keywords: compensation, transformational leadership, performance, job satisfaction.Â